Avaliação da biodegradabilidade de produtos à base de mandioca e mamona - Ghem, Jorge Luiz Dutra (2006)
The products biodegradability produced to leave derived from cassava and ricinus are biodegradability for the constitution of the polimerics chains. They constitute a viable alternative in substitution, instead polymers biodegradability of food packings, for the reduction of the great amount of generated solid residues. It is important to emphasize the necessity of accomplishment tests, in order to know better the mechanisms of the products biodegradability. The tests in half inert solid of vermiculita simulate the ambient conditions next to the reality, in relation to the other ways. This experiment development focus to establish an evaluation of the materials biodegradability from cassava starch and ricinus in order to get information that may contribute in perfectioning and election for biopolimers use. The evaluated materials in half solid of vermiculita with aeration system 45ºC, with 45 mL of inoculo extracted from composting residue material from pruning trees. The carbonic gas unfastened in the degradation, determined the CO2 absorbed mass in solution of barium hidroxid 0,0125 moL/L and titleholder with solution standard of cloridric acid 0,05 mol/L, using phenolftalein indicating in order to determine the changing point. The degradation taxes, according to ASTM norms and ISO, 60% of the polymer Carbon must be mineralized in CO2, the biodegradability standards are satisfactory. The trays with cassava starch, 66,44% and starch with film, 62,36%. The ricinus trays, 13,82%, even though the biodegradability, did not reach a biodegradability index, chemical and physical composition was attributed to a ricinus polymer when degradated, did not suffer intrinsic influence from bacterial activity.